Review of the book: Human Rights Education in the School System of Europe, Central Asia and North America: A Compendium of Good Practice. Warsaw: Poligrafus Andkzey Adamica, 2009. 238 p. - A. H. Saidov; F. Hamdamova (Московский журнал международного права, 2010)
The book has been prepared on the initiative of the Office for Democratic Institutions and Human Rights of the Organization for Security and Cooperation in Europe (OSCE/ODIHR), the Council of Europe, OHCHR and UNESCO). The volume holds long and unique experience of these international organizations in creating and developing human rights education system.